ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. FAJAR PIKIRAN RAKYAT KOTA SERANG - Angrian Permana; Rizky Arief (Jurnal Ilmiah Manajemen dan Bisnis, 2018)
This study aims to determine how much influence of TransformationalLeadership and Compensation to Job Satisfaction Employees at PT. Fajar PikiranRakyat. The independent variable is Transformational Leadership as (X), andCompensation as (X) and the dependent variable is Employee Satisfaction (Y).The method used is a quantitative descriptive method that aims to determinewhether there is the influence of the independent variable that isTransformational Leadership and Compensation to the dependent variable of JobSatisfaction. The unit of analysis used is employees of PT. Fajar Pikiran Rakyat,with a total population of 54 employees who are also taken as a sample.Technical analysis of data used is descriptive statistics, classical assumption test,the coefficient of determination, multiple linear regression analysis, andhypothesis testing. The result of this research can be concluded thatTransformational Leadership variable has a significant effect on Job Satisfactionvariable, Compensation variable has significant effect to Job Satisfactionvariable, Transformational Leadership variable and Compensation havesignificant influence simultaneously to Job Satisfaction variable.